Static Spherically Symmetric Charged Fluid Sphere in Einstein-Cartan Maxwell Theory: Investigating the Interior Field and Physical Constants of a Charged Fluid Sphere in Einstein-Cartan Theory (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present paper deals with charged fluid sphere in Einstein-Cartan theory. In this paper, we have studied the interior field of a static spherically symmetric charged fluid distribution with spin. Assuming that the spin of the individual particles compositing the fluids are all aligned along radial direction, we have obtained solutions by choosing metric potential α(r) and β(r) on different suitable forms or conditions. Pressure and density have been also calculated for the distribution and the physical constants appearing in the solution have been evaluated by matching the solutions to the Reissner-Nordstrom metric at the boundary. It is found that for a realistic model p > 0, p > 0, which will impose further restrictions on our solutions.